Kajian Konsumsi Bahan Bakar Dump Truck pada Pengangkutan Ore Bauksit di PT. Antam Tbk UBP Bauksit Tayan, Kalimantan Barat - Halawa, Juliani; Syahrudin, Syahrudin; Purwoko, Budhi (Jurnal Teknologi Lingkungan Lahan Basah, 2026)
In mining operations, mechanical equipment is essential. One of the mechanical pieces of equipment used in the hauling process, particularly in the open-pit mine of PT ANTAM Tbk UBPB Tayan, is the dump truck. A crucial component of the hauling activity is the fuel required by the hauling equipment. This study aims to determine the fuel consumption (liters/hour) of the hauling equipment and to analyze the fuel costs incurred during the transportation of bauxite ore. Several factors, including road grade, influence fuel consumption. Based on field observations, 4 out of 17 road segments exceeded the company's recommended maximum road grade of 10%. Other factors affecting fuel consumption include idle time, rimpull usage, power, and operator behavior towards the hauling equipment. The fuel consumption was calculated using rimpull and idle RPM. Based on rimpull and idle RPM calculations, the fuel consumption of the Hino 500 dump truck is 8.71 liters/hour, with a fuel cost of IDR 134,850/hour. The hauling equipment productivity is 70.23 tons/hour, resulting in a fuel ratio of 0.12 liters/ton and a hauling cost of IDR 1,860 per ton. After simulating improvements in road grade and idle time, fuel consumption decreased to 7.39 liters/hour, with a fuel cost of IDR 114,545/hour. The productivity of the hauling equipment after idle time improvement increased to 93.56 tons/hour, resulting in a post-improvement fuel ratio of 0.08 liters/ton and a hauling cost of IDR 1,240 per ton.